Analysis of Etiology and Risk Factors of Catheter-Associated Urinary Tract Infection in Critically Ill Patients and Research on Corresponding Prevention and Nursing Measures - Du Juanjuan; Zhao TianTian; Dong Yue; Wang Lili; Xu Ping; Hongyun Xu (Applied Bionics and Biomechanics)
Catheter-associated urinary tract infection (CAUTI) is the most common complication in patients with indwelling catheterization. The incidence of CAUTI in my country is still at a relatively high level compared with foreign countries, especially for the ICU, which has a high usage rate of urinary catheters, to focus on prevention and control. This article focuses on studying the risk factors of CAUTI in critically ill patients and discusses targeted preventive care measures. This article investigates and examines the clinical data of CAUTI in critically ill patients. After statistical analysis, the risk factors that affect CAUTI are summarized, so as to derive the cause of CAUTI in order to strengthen clinical care and to further study the prevention, control, and nursing of CAUTI to provide reference. Clinical data shows that the CAUTI infection rate of patients with catheter indwelling ≥7 days is greater than that of patients with catheter indwelling days less than 7 days. The CAUTI infection rate of the patients who change the urine collection bag every day or ≥7 days is greater than that of the patients who change the urine collection bag within 2 to 4 days.